2008
DOI: 10.1038/ncpendmet0730
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and metabolic benefits with diets of varying fat and carbohydrate content: separating the wheat from the chaff

Abstract: With the rising prevalence of both obesity and diabetes, the contributing role of diet to the prevention and treatment of these conditions has become a major focus of research, clinical practice, and public policy. There has been intense debate over which dietary regimens might be most effective for weight loss, with interest centered on the potential for specific dietary macronutrients to affect body composition, metabolism, and overall health. This Review addresses two regimens with distinct macronutrient pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…In modern western societies, wheat is the major whole grain consumed. The bran and germ of whole wheat are widely accepted as important ingredients in many low glycaemic index (GI) foods (Brehm & D'Alessio, 2008;Jenkins et al, 1986;Jimenez-Cruz, Bacardi-Gascon, Turnbull, Rosales-Garay, & Severino-Lugo, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In modern western societies, wheat is the major whole grain consumed. The bran and germ of whole wheat are widely accepted as important ingredients in many low glycaemic index (GI) foods (Brehm & D'Alessio, 2008;Jenkins et al, 1986;Jimenez-Cruz, Bacardi-Gascon, Turnbull, Rosales-Garay, & Severino-Lugo, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Based on the aforementioned new findings, these official recommendations have now been questioned [9-11]. Several randomized, controlled studies have shown greater weight loss and better improvement of cardiovascular risk parameters with energy-restricted low-carbohydrate diets compared to energy-restricted low-fat diets after treatment periods of six to twelve months [12-15].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidaemia also is usually improved in case of weight loss [16]; our weight loss group normalised completely their lipid values.…”
Section: Discussionmentioning
confidence: 99%